Study of Pedestrian Path Connectivity Using Urban Network Analysis in the Bojong Gede Station Area, Bogor - nasri hamzah, andi; Hadi Prabowo, Ahmad (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The Bojong Gede area, which is the current research location, is a mixed area consisting of stations, terminals, markets, shopping centers, education, offices, and housing. The urban layout occurs naturally without an overall urban layout concept. This study aims to identify spatial characteristics and factors that affect connectivity on pedestrian paths in the area around Bojong Gede station. To determine the level of connectivity, the Urban Network Analysis (UNA) tool is used, which is a quantitative analysis that includes three main elements in an urban area, namely roads, intersections, and buildings that represent the built environment. UNA is used to assess environmental quality quantitatively. This includes unplanned areas such as Bojong Gede. The results of the analysis are in the form of potential and problems that will be followed up with design proposals. The UNA study is then compared with the criteria of urban design elements, because the indicators resulting from UNA cannot stand alone to interpret the results of the analysis. The results show that UNA is very effective in assessing the quality of organically growing urban environments.